Rapidly progressive pulmonary hypertension and right ventricular failure in a heart and kidney transplant recipient. Issue 12 (5th December 2022) - Deicke, Matthew; Alhuneafat, Laith; Obaid, Omar; Adeniyi, Aderonke; Raina, Amresh; Kassis‐George, Hayah
Abstract: A 54‐year‐old man status post heart and kidney transplant presented with dyspnea. Imaging was consistent with lymphangitic carcinomatosis (LC), in the setting of biopsy proven adenocarcinoma. He developed pulmonary hypertension (PH) and died of right ventricular failure (RVF) 3 weeks later. Acute PH with radiographic features of LC in a high‐risk patient warrants expedited malignancy investigation. Abstract : Lymphangitic carcinomatosis is an under‐recognized manifestation of metastatic malignancy—resulting in fatal pulmonary hypertension and right ventricular failure—thus necessitating consistent and aggressive cancer screening in high‐risk patients, such as those who are immunocompromised and have a higher likelihood of the development of cancer.